ENERGY MANAGEMENT AS A TOOL FOR ENSURING SUSTAINABLE DEVELOPMENT AND ENERGY INDEPENDENCE OF UKRAINE - Кузнецова, Інна (Forestry Education and Science: Current Challenges and Development Prospects, 2026)
The transformation of the global economic model in the conditions of depletion of energy resources and increased requirements for sustainable development is studied. The strategic importance of energy efficiency for Ukraine as a foundation of national security and energy independence in the conditions of war and post-war recovery is substantiated. The structure of energy consumption and the regulatory and legal field are analyzed, in particular the ISO 50001 standards. The author scientifically substantiates the composition of the elements of the energy management system (policy, analysis, monitoring, organizational structure, resources) based on the principles of system management and the PDCA methodology (Deming cycle). A characteristic of the elements of the energy management system is provided. An approach to the formation of internal standards and corrective actions is proposed, which allows transforming energy management into an adaptive tool for increasing the energy efficiency of the organization.